The taming of Leviathan: Competition among governments - Stefan Sinn (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1990)
This paper develops a model of governments in competition. With its help I hope to throw some light on the question of whether economists should advocate coordination or competition among governments. My conclusion will be a plea for less harmonization and more competition, a conclusion that I derive from the model presented. For the main part my analysis is a positive one: I present a model that I believe captures the situation of governments, voters and firms acting within a global economy characterized by a high mobility of capital.
Keywords: 330